The function of marked word order in biblical Hebrew prose : an evaluation of existing theories in the light of 2 Kings - Jackson, Leolyn M.(Leolyn Martin) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.A.) -- University of Stellenbosch, 1996.